CONJUGATION OF THE COUNTRIES OF THE EURASIAN ECONOMIC UNION AND CASPIAN REGION - E. E. Golovina; S. A. Velikaia (Современная наука и инновации, 2022)
The Eurasian Economic Union as an international organization of regional economic integration is the middle space within which the global project of the Greater Eurasian Partnership is formed. The triad of Eurasian states of the EAEU (Russia, Belarus and Kazakhstan) form the basis of this Union and the integration potential of its development. The specifics of the EAEU geographical space is in conjunction with the most important international organizations of Eurasia, within the geopolitical and economic boundaries of which the Shanghai Cooperation Organization (SCO), the Commonwealth of Independent States (CIS), the European Union (EU) and others are developing. A special place is occupied by the informal association of the Caspian Region states (CRS), where the geopolitical project " The Greater Caspian Region" is being formed. In the framework of this configuration possible approaches to the conjugation of the most important segments of the EEU and the Caspian region development are considered.